RISK ANALYSIS BY COMBINING FAULT TREE ANALYSIS (FTA) AND ANALYTIC HIERARCHY PROCESS (AHP) METHOD APPLICABLE TO CANE CUTTER MACHINE - Novareza, Oyong; Revadi, Chindy Elsanna; Efranto, Remba Yanuar (JEMIS (Journal of Engineering & Management in Industrial System), 2017)
2000 times of downtime had been occurred during year 2013 to 2014 in Tjoekir sugar factory. The most serious downtime occurred in mill. Fault Tree Analysis (FTA) was employed to analyze the probability score and implement Analytic Hierarchy Process (AHP) to find out impact score of risk event. The results of FTA indicate that risk event in cane cutter blade had the highest probability score, while results of AHP shows that the decrease of steam pressure in turbine drive had the highest impact score. The scores classified in risk class and mapped in risk matrix show that there were three risk events. Tjoekir has to set a conveyor gate to filter canes before being received by the machine, use blades with the thickness not exceed 22 cm to avoid fatigue, and check harvested cane thoroughly that is loaded onto carriers to ensure no machete is accidently loaded with the cane.